Predictors of Adherence to Diabetes Self‐Care Management Among Diabetes Patients in Public Health Facilities of Central Ethiopia: A Multicenter Cross‐Sectional Study - Arega Abebe Lonsako; Bereket Samuel; Abdurehman Ayele; Tsehaynew Kasse; Addisalem Haile (Lifestyle Medicine)
ABSTRACT Background Diabetes mellitus is a global public health challenge. Adherence to self‐care management is critical to reducing complications. Evidence on adherence levels and influencing factors among diabetes patients in central Ethiopia is scarce. This study assessed adherence levels and predictors among diabetes patients in Kembata Zone, Central Ethiopia. Methods A multicenter cross‐sectional study was conducted from May 1 to 30, 2024, involving 414 diabetes patients. Data were collected via interviewer‐administered questionnaires and analyzed using Statistical Package for Social Science (SPSS) version 26. Systematic random sampling was employed, and multivariable logistic regression identified adherence predictors. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated, with statistical significance set at p < 0.05. Results Overall good adherence to diabetes self‐care was 24.4% (95% CI: 20.3–28.5). Adherence by domain was 35.5% for dietary management, 20.5% for exercise, 42.3% for hypoglycemia management, 24.9% for insulin administration, and 29.7% for blood glucose testing. Urban residence (AOR = 1.70, 95% CI: 1.02–2.84) and diabetes duration of 1–5 years (AOR = 2.99, 95% CI: 1.39–6.48) positively predicted adherence, whereas primary education was negatively associated (AOR = 0.33, 95% CI: 0.15–0.74). Conclusions Adherence to diabetes self‐care management in the study area was low, particularly in exercise and insulin administration. Urban residence and shorter diabetes duration were positive predictors, whereas lower education hindered adherence. Urgent health education tailored to rural and less‐educated populations is needed, emphasizing exercise and insulin management to improve outcomes.